A UV‐LEDs based photomicroreactor for mechanistic insights and kinetic studies in the norbornadiene photoisomerization. Issue 2 (6th November 2019) - Shen, Chong; Shang, Minjing; Zhang, Hong; Su, Yuanhai
Abstract: In this work, we report a simple and inexpensive UV‐LEDs based photomicroreactor assembly constructed by commercially available components. The photoisomerization of norbornadiene to quadricyclane was selected to validate this novel photomicroreactor design. Mass transport limitation was eliminated and indicated by dimensionless numbers Fo and Da II, and photons loss was evaluated considering the absorption and reflection of the microreactor walls. The solvents, photosensitizers, and light sources selections were optimized for achieving better photochemical performance and mechanistic insights. The detailed comparison between the high‐pressure mercury arc lamp and the UV‐LEDs strip revealed great potential of UV‐LEDs as appealing light source for photochemical transformations. Moreover, the reaction mechanism was thoroughly discussed and illustrated by the Jablonski diagram indicating electronic states transitions. According to possible intermediate steps, a kinetic model was proposed with the reaction rate constant being correlated with the photon flux, which is valuable for process optimization and further understanding reaction mechanisms.